A Hydrogeochemistry Analysis for Quality Determination of Shallow Karstic Groundwater in Western Tuban, Indonesia - Pambudi, Setia; Sulistijo, Budi; Iskandar, Irwan; Yudiantoro, Dwi Fitri; Haty, Intan Paramita; Ekasara, Adam Raka; Afrilita; Yoni, Dian Rahma; Pratomo, Septyo Uji (UIR PRESS, 2024)
Groundwater hydrogeochemistry and water quality assessment have been conducted in western Tuban, Indonesia, which is characterized by its karstic features based on physicochemical parameters (pH, electric conductivity, total dissolved solids, hardness, Ca2+, Mg2+, Fe3+, Mn2+, K+, Na+, Li+, NH4+, HCO3-, Cl-, SO42-, NO2-, and NO3-) from 25 shallow groundwater samples. The Piper diagram implies the groundwater is of HCO3–Ca+Mg type with some Na+K–SO4+Cl type meaning that the groundwater in Western Tuban is influenced by the silicate minerals weathering, the dissolution of carbonate lithology, and seawater intrusion. Durov diagram shows that the evolution of groundwater is influenced by ion exchange with clay minerals and by mixing with seawater. The Gibbs diagram indicates that the change in the chemistry and quality of groundwater is caused by a dominance of rock-water interaction in the Western Tuban. The water quality assessment based on the USSL and Wilcox diagrams indicates a high level of salinity and relatively low sodium, meaning that the suggested crops should have good salt tolerance, and the cultivated soil should still be able to handle the relatively low sodium level for irrigation.